The Effects of School-based Management in the Philippines : An Initial Assessment Using Administrative Data - Khattri, Nidhi; Ling, Cristina; Jha, Shreyasi (Taylor and Francis, 2013)
This paper estimates the effect of school-based management on student performance in the Philippines using the administrative dataset of all public schools in 23 school districts over a three-year period, 2003–2005. The authors test whether schools that received early school-based management interventions (training in school-based management and direct funding for school-based reforms, based on school improvement plans) attained higher average test scores than those that did not receive such inputs. The analysis uses school-level overall composite test scores (comprising all subject areas tested) and test scores in three separate subject areas: English, mathematics, and science. Their preferred estimator, difference-in-difference with propensity score matching, shows that the average treatment effect of participation in school-based management was higher by 1.5 percentage points for overall composite scores, 1.2 percentage points for mathematics scores, 1.4 percentage points for English scores, and 1.8 percentage points for science scores. These results suggest that the introduction of school-based management had a statistically significant, albeit small, overall positive effect on average school-level test scores in 23 school districts in the Philippines. The paper provides a first glimpse of the potential for school-based management in a Southeast Asian context based on available administrative data. The authors suggest that the next order of research is to answer policy-related questions regarding the reforms: what aspects of the reform lead to desired results; are there differential effects across subpopulations; and what are the potential downsides to the reforms? The authors recommend that countries embarking on implementation of school-based management reforms specify their school-based management model and theories of change clearly and advance mechanisms for rigorous evaluations simultaneously. Such evaluations should not only provide more accurate estimates of the effectiveness of the reforms, but also help answer policy-related questions regarding design and implementation of those reforms in different sociocultural contexts.